Comparisons of Impact of Vein Grafting with Different Indications on Outcomes of Reconstruction with Free Flaps - Coriddi, Michelle; Kim, Leslie; Haglich, Kathryn; Nelson, Jonas; Shahzad, Farooq; Dayan, Joseph; Disa, Joseph; Mehrara, Babak; Cordeiro, Peter; McCarthy, Colleen (Journal of Reconstructive Microsurgery, 2024)
Background Prior studies have shown an increased risk of complications and flap loss with the use of vein grafts in microsurgery. We hypothesize that indication for use of a vein graft can affect flap complications and loss rates.Methods We performed a retrospective review of all patients at our institution from 2010 to 2020 who underwent free flap reconstruction and required use of a vein graft. Indications for vein grafting included: salvage of flap during primary operation after microvascular compromise, augmentation of flow during primary operation, lengthening of the flap pedicle during the primary operation, and salvage of the flap during a secondary salvage operation after microvascular compromise.Results A total of 79 patients met the study inclusion criteria. There were significant differences among the vein graft indication groups and the following: area of reconstruction (p = 0.002), vein graft length (p = 0.018), vessels grafted (p = 0.001), vein graft donor site (p = 0.011), and total flap loss (p = 0.047). Of the four indications for vein grafting, salvage of the flap during secondary salvage operation after microvascular compromise had the highest rate of total flap loss (26.7%). There were no significant associations between other flap complications and vein graft indications.Conclusion Vein graft use in the primary reconstructive setting is efficacious, with low risk of thrombosis. Use in secondary procedures, however, is associated with higher rates of total flap loss, likely due to the thrombotic process, which was initiated prior to the use of the graft resulting in the salvage procedure and not secondary to the graft itself.
Keywords: vein graft; microvascular reconstruction